MELAWAN MITOS PARADIGMA PEMBANGUNAN BERKELANJUTAN DENGAN PENDEKATAN LINGKUNGAN PROFETIK - Fathoni Fathoni (Nizham Jurnal Studi Keislaman, 2016)
Globalization with its liberalism-capitalistic concept promotes us about materialism that everything has to count as matter. Including how is their perspective about the relation between the human and environment. It is inevitable that environment just as object to emerge the benefit for human being and their life. This paradigm emerges the concept of sustainable development to emphasize and strengthen the link between the conservation of natural ecosystems and human development. The concept of sustainable development as such has been on the scene since at least 1987 when the World Commission on Environment and Development published the Brundtland Report. The substance of "development" becomes more dominant than the substance "sustainable" of "environment" it self, so that we need a concept of Prophetical Environmental Approach, which esteems the environment on sight of development as God's legacy for being kept its eternality. Method: This protocol outlines the methodology for a systematic mapping exercise to identify the research studies measuring the sustainable development approach and comparing it with prophetical environmental approach. Our primary research questions are: what is the rationale of sustainable concept? Why does the environment become worse? Is the Prophetic Environmental Approach worth to be new alternative on environmental paradigm? Based on that research questions, this research will search and compile the primary literature (journals), both international and national related to the topic of sustainable development.